Repurposing of Drugs for Antibacterial Activities on Selected ESKAPE Bacteria Staphylococcus aureus and Pseudomonas aeruginosa - Bridget Kamurai; Molly Mombeshora; Stanley Mukanganyama (International Journal of Microbiology)
Increasing cases of multidrug-resistant pathogens have evolved into a global health crisis. ESKAPE group of bacteria are associated with antibiotic resistance, and infections caused by these pathogens result in high mortality and morbidity. However, de novo synthesis of antibiotics is expensive and time-consuming since the development of a new drug has to go through several clinical trials. Repurposing of old drugs for the treatment of antimicrobial resistant pathogens has been explored as an alternative strategy in the field of antimicrobial drug discovery. Ten non-antimicrobial compounds were screened for antibacterial activity on two ESKAPE organisms, Staphylococcus aureus and Pseudomonas aeruginosa. The drugs used in this study were amodiaquine an antimalarial drug, probenecid used to prevent gout, ibuprofen a painkiller, 2-amino-5-chlorobenzaxazole used as a tool for assessing hepatic cytochrome P450 activity in rodents, ellargic acid an antioxidant, quercetin an antioxidant and anti-inflammatory drug, N–N diacryloylpiperazine used to crosslink polyacrylamide gel in 2D-protein electrophoresis, epicatechin an antioxidant and antiviral drug, curcumin an anticancer drug, and quinine an antimalarial drug. Antibacterial susceptibility tests were carried out for the 10 compounds. Curcumin exhibited the most potent antimicrobial activity against both bacteria, with MICs of 50 μg/ml and 100 μg/ml for P. aeruginosa and S. aureus, respectively. Ellargic acid was found to have an MIC of 100 μg/ml against S. aureus. Curcumin caused protein and nucleic acid leakage from the bacterial cell membrane in both bacterial species. When curcumin was combined with ciprofloxacin, it was found to enhance the antibacterial effects of ciprofloxacin. The combination with ciprofloxacin reduced the MIC for ciprofloxacin from 0.5 μg/ml to 0.0625 μg/ml on P. aeruginosa and 0.25 μg/ml to 0.0625 μg/ml on S. aureus. The results obtained show that curcumin has antibacterial activity against S. aureus and P. aeruginosa and may enhance the antibacterial activity of ciprofloxacin.